Heart Rate Variability in Obese and Non-Obese School Children: Relationship with Hypertension - Graceline Margarat Lydia Shadrack; Latha R; TamilSelvan K; Karthika Priyadharshini U; Jayamala AK; Niveatha S (The Bioscan, 2025)
Background: The incidence of childhood obesity is on the rising trend and obese children are more vulnerable to various health disorders such as heart disease, stroke, diabetes and hypertension. As obesity and family history of hypertension are known to influence the cardiovascular health, this study was designed to assess the alteration in the cardiovascular autonomic function in the obese children with and without family history of hypertension by comparing their HRV parameters with the HRV of non-obese counterparts. Materials and Methods: This cross-sectional observational study was conducted in children of age group 9-19 years (160 subjects) in a private school in Ariyur, Puducherry. Children were divided into 4 groups with 40 subjects in each group. (Obese children with no family history of hypertension, obese children with family history of hypertension, non-obese children with no family history of hypertension and non-obese children with family history of hypertension). Height, Weight, Waist circumference, Waist Hip ratio, skin fold thickness, blood Pressure in supine and standing position, Resting Heart Rate, values were measured. ECG was recorded in Lead II configuration in supine posture for 5 minutes and then on standing for 5 min, using PHYSIOPAC PP4 MEDICAID system CHANDIGARH. Results: Our findings showed that there is a significant decrease in Mean RR, SDNN, RMSSD, PNN50, in non-obese children with family history of hypertension. This shows that there is altered sympathovagal balance in obese children with and without family history of hypertension and also in non-obese with family history of hypertension. Conclusion: From our study, we observed that there is alteration in sympathovagal balance among the obese and non-obese children with positive family history of hypertension and also in obese without family history of hypertension. As a result, they may suffer from increased cardiovascular morbidity. Hence Periodic assessment of HRV in this vulnerable population can help detect early changes in cardiovascular health whereby timely interventions could be implemented and vital advices on weight reduction and regular exercise could be provided to avert the risk of cardiovascular disease in them.